Lepidine Orange derivative as a new dye for sensitive fluorescent detection of DNA - Didan, Yu.V.; Kryvorotenko, D.V.; Negrutska, V.V.; Dubey, I.Ya. (Вiopolymers and Cell, 2013)
Aim. To study new cyanine dye LO-7 as a reagent for dsDNA visualization in electrophoretic gels. Methods. Gel electrophoresis, restriction, fluorescence detection, mobility shift assay. Results. LO-7 binds to DNA to form stable highly fluorescent complexes. As little as 80 pg DNA can be detected in LO-7-stained agarose gel using a laser scanner, and 0.3 ng with UV-transilluminator. This sensitivity is several times higher than can be achieved with ethidium bromide, and close to that of SYBR Green I. Conclusions. LO-7 belongs to the most efficient stains for dsDNA visualization and thus can be used in bioanalytical applications where high sensitivity is required. Мета. Дослідження нового ціанінового барвника LO-7 як реагента при візуалізації дволанцюгової ДНК в електрофоретичних гелях. Методи. Гель-електрофорез, рестрикція, флуоресцентна детекція, mobility shift (зміна електрофоретичної рухливості). Результати. LO-7 зв’язується з ДНК, утворюючи стійкі високофлуоресцентні комплекси. У пофарбованих ним агарозних гелях можна визначати ~ 80 пг ДНК за допомогою лазерного сканера і 0,3 нг – за використання УФ-трансілюмінатора. Подібна чутливість у кілька разів вища, ніж у бромистого етидію, і близька до такої для SYBR Green I. Висновки. LO-7 належить до найефективіших барвників для візуалізації дволанцюгової ДНК і може застосовуватись при вирішенні біоаналітичних завдань, де необхідна висока чутливість. Цель. Изучение нового цианинового красителя LO-7 как реагента при визуализации двухцепочечной ДНК в электрофоретических гелях. Методы. Гель-электрофорез, рестрикция, флуоресцентная детекция, mobility shift (изменение электро- форетической подвижности). Результаты. LO-7 связывается с ДНК, образуя устойчивые высокофлуоресцентные комплексы. В окрашенных им агарозных гелях можно определить ~ 80 пг ДНК при помощи лазерного сканера и 0,3 нг – при использовании УФ-трансиллюминатора. Подобная чувствительность в несколько раз выше, чем у бромистого этидия, и близка к таковой для SYBR Green I. Выводы. LO-7 принадлежит к наиболее эффективным красителям для визуализации двухцепочечной ДНК и может применяться для решения биоаналитических задач, где необходима высокая чувствительность.